PENGARUH PROFITABILITAS DAN FINANCIAL LEVERAGE PADA INCOME SMOOTHING DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL PEMODERASI - Ulfa Tsuroyya, Mutiara; Putra Astika, Ida Bagus (E-Jurnal Akuntansi; Vol 20 No 3 (2017), 2017)
Income smoothing is an action taken by management to increase and decrease profits to create a stable corporate profits that reflected good performance for investors. The purpose of this study to determine the firm size able to moderate the effect of profitability and financial leverage on income smoothing. This research was conducted on a company listed on the Stock Index KOMPAS100 period 2013-2015. The samples in this study was 78 samples were selected by purposive sampling method. Data analysis techniques used is the logistic regression analysis using the interaction test (Moderated Regression Analysis). The results of this study showed the profitability of a positive effect on income smoothing, financial leverage has no effect on income, the firm size able to moderate or weaken the effect of profitability on income smoothing, the firm size is not able to moderate the effect of profitability on income.
Keywords: Income Smoothing, Profitability, Financial Leverage, Firm Size